(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This study is conducted to evaluate corrosion and scaling potentials of raw and treated water at Al-Tayyaraa water treatment plant during a period of twelve months, starting from January to December 2016. Three indices of corrosion and scaling in this study are considered including Ryznar Index (RI), Langelier Saturation Index (LSI), and Aggressive Index (AI). Water quality parameters pH, Alk, (Ca), temperature, calcium as CaCO3, and (TDS) are measured. For raw water, the values of LSI and RI are (0.14-0.504) and (6.956 -7.62), respectively, whereas for treated water, the values of LSI and RI are (0.03-0.4) and (7.02-7.7), respectively. The values of AI are (11.77-12) for raw water and (11.67-11.948) for treated water. The calculated values of Langelier Saturation Index (LSI) reveal that the treated and raw water are balanced to some faint coating (light scale forming). The values of RI point that the raw and treated water are corrosive and values of aggressive index show that the water is moderate corrosion and no obvious effect on concrete tank at water treatment plants.